Giving A Face to Chemotherapy-Induced Alopecia: A Feasibility Study on Drawings by Patients - Kirsten van Alphen; Anne Versluis; Wouter Dercksen; Henk de Haas; Rieneke Lugtenberg; Jitske Tiemensma; Judith Kroep; Elizabeth Broadbent; Ad A Kaptein; Corina van den Hurk (Elsevier, 2020)
Objective: Individuals with cancer experience the impact of chemotherapy on hair loss in different ways. The aim of this pilot study was to explore patients' experiences of alopecia through patients' drawings. Methods: Fifteen female patients diagnosed with cancer and treated with chemotherapy were recruited at the oncological day-care unit of a teaching hospital in the Netherlands. Participants completed a semi-structured interview about alopecia. They drew their head and hair before and during chemotherapy and completed the Brief Illness Perception Questionnaire (B-IPQ).Results: The drawings revealed predominantly physical effects, rather than emotions. Emotions were evident in the text that patients wrote under the drawings and in the B-IPQ open question about the perceived consequences of alopecia. The overall impact of alopecia that emerged from the drawings and the B-IPQ corresponded to the information retrieved from the interviews, namely disappointment, insecurity, sadness, and confrontation.Conclusions: Drawings expose cognitive and emotional responses to alopecia that may be relatively unexplored when using traditional assessment methods such as questionnaires or interviews. In future research, the drawing instructions need to be more specifically focused on feelings in order to better capture emotional reactions to hair loss.